The Relationship Between The Use of Cotton Bud and Obturation Cerumen in Prima Indonesia University Faculty of Medicine Students, Class of 2021 - Siregar, Gymnastiar; Tambunan, Andika Zayani; Lubis, Yuliani Mardiati; Aishwara, R. Naina (Fakultas Kedokteran Universitas Malikussaleh, 2024)
The use of cotton buds is considered to be able to cause cerumen impaction in the external ear canal. However, the use of cotton buds in Indonesia is still quite high. This study aims to examines the relationship between the use of cotton buds and the incidence of cerumen obturans. This study used a cross-sectional study design involving 56 respondents who routinely use cotton buds. Based on the study, a significant relationship was obtained between the frequency and depth (p-value 0.026 and p-value 0.008) of cotton bud use and the incidence of cerumen obturans. Students who frequently use cotton buds have a 5.625 times greater risk of experiencing cerumen obturans compared to those who rarely use them. Students who use cotton buds up to the pars osseus (2/3 of the inner ear canal) have a 4.444 times greater risk of experiencing cerumen obturans compared to those who only use cotton buds up to the pars cartilaginosa (1/3 of the outer ear canal). In conclusion, health education programs regarding the use of cotton buds need to be developed to increase awareness of how to maintain safe and effective ear hygiene.